The Role of Human Resource Information Systems (HRIS) in Improving Employee Performance: A Systematic Literature Review - AS, Falga Bara Prima Abadi; Hamdani, Hamdani; Lestari, Dirga (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
As modern enterprises embrace digital transformation, Human Resource Information Systems (HRIS) have become essential for managing organizational talent. This systematic literature review synthesizes empirical evidence from 30 academic papers and three foundational texts published between 2021 and 2026, explicitly examining how digital HR infrastructures elevate individual workforce achievements. Utilizing the PRISMA protocol, the study extracts data across multiple global databases to map the direct impacts and underlying mechanisms linking system utilization to employee productivity. Comprehensive analysis confirms that digital HR platforms significantly boost staff effectiveness by optimizing administrative routines, elevating data precision, and upgrading evaluation protocols. Crucially, these technological advantages translate into individual success primarily through intermediate channels, including workplace contentment, active engagement, and superior strategic judgments. Furthermore, organizations only realize these benefits when supported by an accommodating corporate culture and flawless technical integration. By assembling previously disconnected findings, this review bridges the gap between technological capabilities and behavioral outcomes, equipping executives with evidence backed strategies for technological governance while outlining a rigorous agenda for future multilevel and longitudinal research.